Parasitasi Trichogramma evanescens Westwood (Hymenoptera : Trichogrammatidae) pada Berbagai Tingkat Populasi dan Generasi Biakan Parasitoid terhadap Telur Penggerek Batang Jagung Ostrinia furnacalis Guenée - PABBAGE, M.S.; TANDIABANG, J. (AGRITROP, 2007)
The parasitoid T. evanescens was reared in the laboratory, then; one, two, three, four, five, six female parasitoidrespectively was released to one hundred eggs of ACB in the tube. The second experiment, the parasitoid wasreared in the laboratory until ten, fifteen, twenty and twenty five generations, than released to one hundred eggs ofACB. The observation was done five days after releasing parasitoid. The result of the experiment showed that themaximum parasitism on the eggs of ACB 53.2% at four female parasitoid per hundred eggs of ACB. The increaseof the number female parasitoid, the parasitism degree per one female parasitoid, and the emergence of the newparasitoid from egg were decreased. The parasitoid T. evanescens that reared in the laboratory by using substitutedhost Corcyra cephalonica was still effective up to tenth generations to control the eggs of ACB. Parasitoid thatrearing after tenth generations, the parasitism degree, the new emergence parasitoid from the egg of ACB andwalking or jumping speed of parasitoid was decrease.